EXPERIENCE OF DEMOCRATIC STATES WITH DEVELOPED SOCIAL COOPERATION - Tashpulat B. Matibaev (International Journal of Innovations in Engineering Research and Technology, 2023)
This article is devoted to the experience of democratic states where social cooperation has developed. Social cooperation arose in connection with the unification of the working class in trade unions and their struggle for their rights. It has acquired different characteristics in different cultures and historical contexts. Western scientists have actively studied this phenomenon in the context of industrialization and democratization of society. Social cooperation is designed to regulate the interests of various social groups and encourage cooperation, not conflict.